CHOLELITHIASIS FOLLOWING BARIATRIC SURGERY: A NEW APPROACH TO DEAL WITH (Iraqi Journal of Medical Sciences, 2017)
Background: Obesity and rapid weight loss induced by weight-reducing surgery are well recognized as a risk factor for the development of gallbladder stones. There is no standard policy whether to perform prophylactic cholecystectomy at the time of the bariatric operation or to give postoperative treatment to decrease the risk.Objective: To evaluate the incidence and risk factors of gallstone formation post-bariatric surgery. The results may help to decide how to deal with and follow up patients with post-bariatric surgery.Methods: A total of 120 patients who underwent weight-reducing operations were recruited for this study. Several factors expected to influence gallstone formation were recorded such as body mass index and excessive weight loss. Study population was followed up for 12 months postoperatively. Ultrasonography examination was performed for those who developed symptoms suggesting gallstone formation.Results: Twenty-six (21.7%) patients were found to develop gallstones. Of the studied risk factors, the percentage of excess weight loss, family history and carrying allele A of the variant rs670 were significant for predicting development of gallstone post-bariatric procedures. Conclusion: Based on the results of this study, it is reasonable to put an index for the risk of developing gallstone following bariatric surgery, and according to this index, the surgeon could decide whether to perform concomitant cholecystectomy along with the bariatric procedure or do not.Keywords: Bariatric surgery, cholelithiasis, single nucleotide polymorphismCitation: Sajid H.A. Al-Helfy, Qasim S. Almayah, Risala H. Allami. Cholelithiasis following bariatric surgery: a new approach to deal with. Iraqi JMS. 2017; Vol. 15(2): 143-150. doi: 10.22578/IJMS.15.2.6
Keywords: Bariatric surgery; cholelithiasis; single nucleotide polymorphism